Remedies used in pharmaceutical practice - important sources contributing to the reconstruction of „Medical Materia” - Taerel, Adriana Elena; Stancu, Emilia; Draganescu, Doina; Carata, Ana (Arhiv za farmaciju, 2022)
Information on remedies used in different periods of time can be obtained directly through consulting the pharmacopoeias. Also, the organizational administrative documents such as inventories are important sources contributing to the reconstruction of „Medical Materia” in time and space. An inventory book elaborated in 1928 was used as documentary material highlighting the remedies used in that period of time in a rural private pharmacy „Elena Deciu”. In parallel with this document the existing Romanian Pharmacopoeia was studied, fourth edition printed in 1926. It was followed to what extent there is synchronization between the remedies used in therapeutic practice and those included in this Pharmacopoeia. Information about some aspects of continuity or discontinuity of some simple and compound remedies listed in the inventory book was obtained by parallel consulting the previous Pharmacopoeias. We found that there is a difference between the remedies used in pharmaceutical practice, as the studied annual accounts book reflects directly in the study and the official rules settled by Pharmacopoeia. Most of the remedies listed in the inventory book are found in the pharmacopoeia of 1926 or in the previous ones, the only exception of our presentation being the injection solution of Sodium Cacodylate which appears in the fifth edition of Pharmacopoeia.